Comportamiento epidemiológico de la Leucosis Bovina en la provincia de Cotopaxi. - Cabezas Racines, Adriana Nicole (2022)
The Bovine Viral Leukosis (BVL) is a highly contagious desease of worlwide distribution that affects both beef and dairy cattle and has a considerable economic impact, since it is related to productive and reproductive parameters of great importance. The main objective was to evaluate the epidemiological behavior of bovine leukosis using the indirect ELISA technique for the diagnosis of the disease in the province of Cotopaxi. The present investigation was carried out in the seven cantons that make up the province of Cotopaxi, in which blood samples were collected from 460 backyard cattle of differen ages, sexes and breeds from the thirty-three parishes that make up each of the cantons of the province, from wich blood sera were obteined. To determine the relationship between risk factors (sex, age and race) and the desease, the chi-square statical metod was aplied. As a result, the prevalence rate in the province of Cotopaxi was 23%, with Sigchos being the most affected canton with a prevalence of 40%, since the parish of Isinliví had a prevalence of 100%, while the canton of La Maná had a lower prevalence of 0%. The risk factor age was the only one that showed a direct relationship with the disease (p ‹ 0.05), showing that the older the cattle are, the greater the probability of becoming infected. With respect to other factors such as breed and sex, no direct relationship was found (p›0,05). Finally the epidemiological map is a tool that helped visually locate the parishes with the hisghest and lowest number of BVL positive animals in Cotopaxi, with Isinliví (15 positive cases) being the parish with the highest number of positive animals.